ANALISA DAMPAK LALU LINTAS TERHADAP RENCANA PENGEMBANGAN KAWASAN PERKANTORAN KOTA MARTAPURA - Bagus Ridhani (Jurnal Teknologi Berkelanjutan, 2018)
Development of office areas in Martapura city is based on the Building and Environmental Planning (RTBL) of Banjar Regency which has a land area of ​​103.5 hectares with a total area of ​​90,270 m2 for government offices. It is suspected that after the office area has been completed and started operating it will have a significant impact on the road network around the area's development. This study aims to predict the magnitude of trip generation / attraction caused by office areas that have been operating, analyze traffic performance on the road network which is expected to be affected by office areas after operation, analyze the impacts caused by the operation of office areas, and provide handling solutions right to maintain a smooth flow of traffic around the office area. Data analysis was performed by collecting traffic flow data and making origin-destination matrix (MAT) using the Detroit method to predict post-construction conditions, 5 years and 10 years post-construction on the road sections reviewed and calculate the level of service at each review year in accordance with predetermined handling scenarios. The amount of traffic generation / movement that occurred was 788 vehicles or 462 SMP / Hour. In the existing condition, the worst service level (D) is Sekumpul Street (Jl. A. Yani), Sekumpul Ujung (Indrasari) road and Martapura Market (Jl. Barakat). The estimated traffic impact caused by the increase in DS ranged from 9.48% to 53.53%. The treatment recommendation that can be given is Scenario number 3 by making exit / entry access on the Alkah road so that the growth of the traffic volume that occurs on the Sekumpul road becomes 12% to 56%.